Handbook of Applied System Science - Neal, Zachary (Taylor & Francis, 2016)
Freshwater eutrophication is one of the major environmental challenges around the world. There is a range of known factors that are responsible, though the increased flux of nutrients from the sources to the water bodies is a key factor. The aim of this study is to operationalize "integrated valuation" as a way of bridging the gap between cost-effectiveness analysis and economic valuation of benefits in implementation of the Water Framework Directive. The authors begin with a definition of integrated valuation model of ecosystem services as a type of systems analysis, before they move on to describe their site of study and the boundaries of their model. Through applied demonstration, the authors evaluate whether the model meets criteria as an integrated valuation tool and discuss further applicability.